2015
DOI: 10.1155/2015/370371
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoexfoliation Syndrome and Pseudoexfoliation Glaucoma: A Review of the Literature with Updates on Surgical Management

Abstract: Pseudoexfoliation syndrome (PES) is a systemic disorder caused by progressive accumulation of extracellular material over various tissues. PES usually determines increased intraocular pressure, changes in the anatomical aspects of the optic nerve, and visual field alterations leading to the diagnosis of pseudoexfoliation glaucoma (PEG). Use of topical medical treatment usually leads to poor results in terms of long-term follow-up but many surgical techniques, such as Argon Laser or Selective Laser Trabeculopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 121 publications
(131 reference statements)
2
50
0
11
Order By: Relevance
“…22 Recent studies have also demonstrated a higher rate of subcapsular cataract in PXFS with respect to non-PXFS eyes. 15 PEX material may be detected earliest on the ciliary processes and zonules. Involvement of zonules can lead to lens subluxation and phacodonesis.…”
Section: Lens Zonules and Ciliary Body Changesmentioning
confidence: 94%
See 2 more Smart Citations
“…22 Recent studies have also demonstrated a higher rate of subcapsular cataract in PXFS with respect to non-PXFS eyes. 15 PEX material may be detected earliest on the ciliary processes and zonules. Involvement of zonules can lead to lens subluxation and phacodonesis.…”
Section: Lens Zonules and Ciliary Body Changesmentioning
confidence: 94%
“…13 Plasma homocysteine level is also increased in PXFS and PXFG and homocysteine level increases with the duration of PXFS. 14 Also, these patients present greater serum concentrations of anti-Helicobacter pylori IgG antibody compared to healthy patients 15 and an elevation of anti-Helicobacter pylori IgG antibody has been demonstrated in the aqueous humour of PXFG and POAG patients. 15 …”
Section: Histology and Proteomicsmentioning
confidence: 97%
See 1 more Smart Citation
“…Ipak, detaljnom opisu ove kliničke slike najviše su doprineli radovi Vogt-a sa karakterističnim sivkastim ili sivo-plaviča-stim pahuljicama na pupilarnoj ivici i/ili membranoznim formacijama na prednjoj kapsuli sočiva, kao i na zadnjoj strani rožnjače. Smatrajući da eksfolijativni materijal potiče od kapsule sočiva i da je povezan sa glaukomom otvorenog ugla, Vogt predlaže termine "senile exfoliatio" i "glaucoma capsulare" (7,8). Termin "pseudoeksfolijativni" prvi put je upotrebila Dvorak-Theobald (1953) u cilju razlikovanja ovih promena od prave eksfolijacije prednje kapsule sočiva koja nastaje kod duvača stakla (8).…”
Section: Ključne Rečiunclassified
“…Smatrajući da eksfolijativni materijal potiče od kapsule sočiva i da je povezan sa glaukomom otvorenog ugla, Vogt predlaže termine "senile exfoliatio" i "glaucoma capsulare" (7,8). Termin "pseudoeksfolijativni" prvi put je upotrebila Dvorak-Theobald (1953) u cilju razlikovanja ovih promena od prave eksfolijacije prednje kapsule sočiva koja nastaje kod duvača stakla (8). Obzirom na mišljenje o verovatno mnogim mestima produkcije ovog materijala, Sunde (1956) predlaže termin "exfoliation syndrome" koji ukazuje na generalizovanu očnu bolest bazalnih membrana.…”
Section: Ključne Rečiunclassified